La salud pública en periodo de crisis (1998)
ABSTRACT: The concepts of public health and crisis are reviewed to conclude that there is not only one definition for each one but also everyone has different historical meanings. It is questioned if public health exists and the answer is affirmative if it is understood as an unfinished and imperfect process with remarkable differences given by the sociological and economical formation in which public health is inserted. The answer to the question concerning whether we are in crisis is affirmative as well. However, in this case, not only the sort of crisis is differentiated but also the condition of the society facing the crisis. When it is questioned if public health is in crisis, the answer states that public health has always been in crisis to date, with important differences form one country to another, since it has never succeeded in fully satisfying wath it tries for with its promotion, prevention, treatment, rehabilitation and investigation functions. Finally, the former analysis is applied to the specific situation of crisis in the Cuban public health, concluding that the crisis situation may also have possitive effecs as in the case of the best utilization of alternative medicines and medicaments, human resource qualification and the increase of physical exercise and diet. The last two have undeniable influences for the individual and for the group health.